Self‐ and informant‐reported cognitive functioning and awareness in subjective cognitive decline, mild cognitive impairment, and very mild Alzheimer disease. (30th October 2019) - Ryu, Seon Young; Kim, Ahro; Kim, SangYun; Park, Kyung Won; Park, Kee Hyung; Youn, Young Chul; Lee, Dong Woo; Lee, Jun‐Young; Lee, Jun Hong; Jeong, Jee Hyang; Choi, Seong Hye; Han, Hyun Jeong; et al.
Abstract : Objectives: The present study examined self‐reports and informant reports of cognitive function and discrepancies between the two reporting methods in healthy controls (HC), subjective cognitive decline (SCD), mild cognitive impairment (MCI), and very mild Alzheimer disease (AD) using three questionnaires. Methods: The study included a total of 300 individuals (mean age: 74.4 ± 5.7 y), including 130 HC, 70 SCD, 51 MCI, and 49 very mild AD patients. Self‐ratings and informant ratings of cognitive function were assessed using the Korean Dementia Screening Questionnaire‐Cognition (KDSQ‐C), AD8, and Subjective Memory Complaints Questionnaire (SMCQ). Awareness of cognitive functioning was measured on the basis of the discrepancy scores between self‐reports and informant reports. Results: Group comparisons on questionnaire scores adjusting for age, education, and depressive symptoms showed that self‐reports were lowest in HC than other groups, with no differences between SCD and MCI groups. Informant reports were lower in SCD than in MCI, while discrepancy scores were higher in SCD than in MCI ( P < .001 for KDSQ‐C and SMCQ; P = .076 for AD8). There were no differences in self‐reports, informant reports, and discrepancy scores between MCI and AD groups. Conclusions: These results support the usefulness of informant‐reported cognitive functioning to classify MCI among elderly with subjective cognitive complaints. In addition, discrepancies between self‐reports and informant reports demonstrate that overestimation and underestimation of cognitive function may serve as a clinical indicator of SCD and MCI across the cognitive continuum, respectively.